2004
DOI: 10.1080/00480169.2004.36390
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ovarian teratoma in a free-living Iberian red deer (Cervus elaphus hispanicus)

Abstract: This case describes the first known description of an ovarian teratoma in a free-living red deer. The tumour had unique features, such as bilateral presence and concurrency with a normal pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Ovarian epithelial neoplasms are uncommon tumors in domestic and nondomestic animals, [1] but have been reported in the bovine, pig, [2] small ruminants, [3] canine, [4] cat, [5] mare, [6] deer, [7,8] and jaguar [9]. Except in the dog, [10] epithelial ovarian tumors occur less frequently than those of mesenchymal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian epithelial neoplasms are uncommon tumors in domestic and nondomestic animals, [1] but have been reported in the bovine, pig, [2] small ruminants, [3] canine, [4] cat, [5] mare, [6] deer, [7,8] and jaguar [9]. Except in the dog, [10] epithelial ovarian tumors occur less frequently than those of mesenchymal origin.…”
Section: Introductionmentioning
confidence: 99%
“…They occur sporadically in a variety of species ranging from amphibia to the mammals (Flux 1965;Bukovjan and Karpenko 1990;Munson and Montali 1991;Karpenko and Bukovjan 1996;Hofle et al 2004;Fitzgerald et al 2007). The finding of an ovarian carcinoma in a badger is unique and to the knowledge of the authors has yet to be reported.…”
mentioning
confidence: 75%
“…Mature ovarian teratomas have also been described in accessory ovaries in women as well as in ovaries of animals. 15,16 Ovarian dermoids continue to surprise us. Some of them are associated with NMDAR encephalitis, a paraneoplastic syndrome in which patients manifest with neuropsychiatric manifestations, which usually resolve after surgical excision of the tumor.…”
mentioning
confidence: 99%